2022
DOI: 10.1097/rct.0000000000001401
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Reconstruction: State-of-the-Art and Future Perspectives

Abstract: Image reconstruction processing in computed tomography (CT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…It effectively removes noisy data, preserves the clarity of structural boundaries, reduces noise resulting from reduced radiation dose, improves image resolution, and maximally maintains image authenticity (34)(35)(36). Studies have shown that iDose 4 reconstruction technology ensures accurate diagnosis while significantly reducing radiation dose (18,37).…”
Section: Discussionmentioning
confidence: 99%
“…It effectively removes noisy data, preserves the clarity of structural boundaries, reduces noise resulting from reduced radiation dose, improves image resolution, and maximally maintains image authenticity (34)(35)(36). Studies have shown that iDose 4 reconstruction technology ensures accurate diagnosis while significantly reducing radiation dose (18,37).…”
Section: Discussionmentioning
confidence: 99%